Sayaw sa Daruhan: Learning Dance Notation from Local Culture of Cebu, Philippines - Navaja, Karl Krist (Jurnal Pendidikan Progresif, 2023)
The main purpose of this study was to produce a dance notation of “Sayaw sa Daruhan” in the context of the Philippines dance notation by Francisca Reyes Aquino. This study aimed to document the Daruhan Dance Festival, its distinctive features and specifically, the study sought to: trace the history of Sayaw sa Daruhan Dance Festival, Describe the Daruhan Dance Festival according to: Basic dance steps, Costumes, Music accompaniment, and produce a dance notation and instructional video of “daruhan festival.” The data being gathered results that this festival being created based on the livelihood of the people in their daily living and the steps being used in the dance were based and mimics the steps on planting and harvesting the soil. Moreover, the results suggested that “Sayaw sa Daruhan must be preserved as the bases or landmark of the barangay and also must be included in the contextualization of school curriculum. Keywords: daruhan, sayaw, festivals, carcar, descriptive methodDOI: http://dx.doi.org/10.23960/jpp.v13.i3.202315